2004
DOI: 10.1210/jc.2004-0021
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor Autoantibodies Are Relevant Markers of Acquired Hypoparathyroidism

Abstract: We investigated the presence of autoantibodies (aAbs) directed against the parathyroid gland in 17 patients with spontaneous isolated acquired hypoparathyroidism. Fourteen patients with acquired hypoparathyroidism (AH) associated with type I or II autoimmune polyendocrinopathy syndrome were also tested in comparison with a control group of 68 subjects without AH, including patients with other autoimmune diseases and healthy blood donors. aAbs against parathyroid tissue were screened using an indirect immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 18 publications
(17 reference statements)
1
42
1
Order By: Relevance
“…Hypoparathyroidism is a heterogeneous group of disorders characterized by tetany, cataract, basal ganglia calcification, hypocalcemia, hyperphosphatemia, and subnormal serum parathyroid hormone (PTH) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Recently, Dolores Shoback has classified its pathophysiologic mechanisms into three broad categories (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoparathyroidism is a heterogeneous group of disorders characterized by tetany, cataract, basal ganglia calcification, hypocalcemia, hyperphosphatemia, and subnormal serum parathyroid hormone (PTH) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Recently, Dolores Shoback has classified its pathophysiologic mechanisms into three broad categories (13).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with isolated hypoparathyroidism (IH) also referred to as acquired or idiopathic hypoparathyroidism demonstrate the presence of CaSR autoantibodies with prevalence varying from 29 to 56% (10)(11)(12). However, they do not demonstrate increased risk of coexisting thyroid autoimmunity unlike in type-1 diabetes and premature ovarian failure (14).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs after thyroid or parathyroid surgery, if all parathyroid tissue is removed; as a consequence of autoimmune disorders, such as antibodies that activate the calcium sensing receptor of the parathyroid glands (1)(2)(3) ; and, more rarely, as a congenital disorder of parathyroid dysgenesis, such as DiGeorge syndrome. (4)(5)(6)(7) Independent of etiology, the typical biochemical constellation in untreated hypoparathyroidism includes low circulating PTH levels, hypocalcemia, relatively high urinary calcium excretion, hyperphosphatemia, and reduced levels of 1,25-dihydroxyvitamin D. (8,9) In the absence of PTH, bone remodeling is reduced.…”
mentioning
confidence: 99%
“…Disor (4)(5)(6). Considering autoimmune hypoparathyroidism, the role of anti-calcium sensor autoimmunity has been challenged (7), but it has also been shown that detection of antibodies against the receptor is influenced by the assay system used (6).…”
Section: Diseases Associated With the Calcium-sensing Receptor Includmentioning
confidence: 99%